2016
DOI: 10.1124/mol.116.103465
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Dopamine Receptor 2 Long Affects Cannabinoid Receptor 1 Signaling in a Cell Culture Model of Striatal Medium Spiny Projection Neurons

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 71 publications
3
23
0
Order By: Relevance
“…These potential physical interactions are obviously cell-type-specific, and can modify the signaling of different pools of CB 1 receptors. In this sense, two recent studies showed how (i) heteromers between CB 1 receptors and adenosine A 2A displays a striking G protein-coupling signaling profile where the stimulation of both receptors reduces the downstream signaling ( Moreno et al , 2017 ); (ii) the formation of heteromers between CB 1 receptors and D2 receptors changes the agonist-mediated CB 1 receptor signaling and coupling ( Bagher et al , 2016 ). More research is needed to better understand the functional impact of the formation of homomers or heteromers between CB 1 receptors and other brain receptors in physiology and pathology.…”
Section: Signaling Of Cb 1 Receptors In the Brain:mentioning
confidence: 99%
“…These potential physical interactions are obviously cell-type-specific, and can modify the signaling of different pools of CB 1 receptors. In this sense, two recent studies showed how (i) heteromers between CB 1 receptors and adenosine A 2A displays a striking G protein-coupling signaling profile where the stimulation of both receptors reduces the downstream signaling ( Moreno et al , 2017 ); (ii) the formation of heteromers between CB 1 receptors and D2 receptors changes the agonist-mediated CB 1 receptor signaling and coupling ( Bagher et al , 2016 ). More research is needed to better understand the functional impact of the formation of homomers or heteromers between CB 1 receptors and other brain receptors in physiology and pathology.…”
Section: Signaling Of Cb 1 Receptors In the Brain:mentioning
confidence: 99%
“…Moreover, ligand bias can be influenced by receptor oligomerization in specific cells or tissues. For instance, CB1-dependent Gα q signaling has been reported to occur through CB1-D2 (type 2 dopamine receptor) dimerization [136].…”
Section: Cb1 Biased Ligandsmentioning
confidence: 99%
“…Despite longstanding consensus as to its canonical Gα i ‐mediated signalling pathway, the type one cannabinoid receptor (CB) is among several GPCRs now understood to transduce signals through more than one G protein effector – a capacity sometimes referred to as ‘promiscuous G protein coupling’ (reviewed in Maudsley et al, ). Environmental and pharmacological conditions that have been found to affect CB 1 receptor signalling in this way include blockade of the canonical Gα i pathway with pertussis toxin (PTX) (Glass and Felder, ; Bonhaus et al, ; Scotter et al, ), the class of CB 1 agonist (Bonhaus et al, ; Lauckner et al, ), receptor oligomers (Kearn et al, ; Bagher et al, ) and cell background (McIntosh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, co‐immunoprecipitation data led Kearn et al () to propose that the CB 1 receptor signalling switch is derived pleiotropically, from altered protein conformations caused by a physical interaction between D 2 and CB 1 receptors – a receptor heterodimer. Characterization of the CB 1 /D 2 receptor heterodimer has continued using other approaches (Marcellino et al, ; Przybyla and Watts, ; Bagher et al, ). It remains noteworthy that the two hypotheses of the signalling switch mechanism need not be mutually exclusive, and both promiscuous (low‐efficacy activation of a non‐preferred G protein species due to lack of availability of the preferred species; i.e.…”
Section: Introductionmentioning
confidence: 99%